Knowledge management capabilities and performance information use in not-for profit organisations / Hamizah Abdul Razak - Abdul Razak, Hamizah (2022)
Not-for profit organisations (NPO) are under increased pressure due to the heightened demand of NPOs to demonstrate results/impact on social services provided. With increased accountability requirements, most NPOs are focusing their efforts on establishing and implementing performance measurement systems. Importantly, when an organisation adopts a performance measurement system, it is expected that the data provided by the system is to be used to secure continuous funding and improve their organisation's social mission deliverables. However, many researchers have documented that only a few NPOs use their performance data relatively low in the strategic decision-making process as volunteers predominantly drive the sector, and volunteers cannot typically run the NPOs. In strategic management literature, knowledge management capability (KMC) is increasingly advocated as strategic management that can empower the human capital in the organisation, resulting in higher use of performance information. However, there has been little research on the effects of knowledge management capabilities (KMC) with performance information (PI) use despite the importance of KMC. Drawing on Resource Dependency theory and Knowledge-based View theory, this paper aim to analyse the relationship between KMC and management performance information (PI) use, focusing on six types of KM infrastructure capabilities: human resource management (HRM), organisational culture, decentralise structure, internal marketing, technology and knowledge leadership and four types of KM process capabilities: acquisition, conversion, application and protection process. The NPOs in Malaysia is chosen due to the increasing importance of the sector to the country's economy in delivering public good to every society and the current government initiatives to empower NPOs to be more independent in funding their social missions. A quantitative approach was conducted using a set of questionnaires that were distributed among the manager/owner/trustee of NPOs. The research model was further analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) technique. Based on the research questions, this study finds HRM, collaborative culture, innovation culture, decentralise structure, technology and protection process has a significant positive influence on management PI use, while the other capabilities elements have no significant link. This thesis contributes to the relevant empirical evidence, which indicates that HRM, collaborative culture, innovation culture, decentralise structure, technological capability and protection process can be the foundation in formulating the overall KMC strategies in NPOs. The results of the proposed study will assist managers by pointing out areas of strength that NPOs can leverage and the policymaker to assess how effective the current policy has been in empowering the NPOs sector to advance this social sector mission deliverable. Overall, the findings in this study provide an important input that can complement the current initiatives in Malaysia to empower NPOs to be more independent in funding and executing their social missions more effectively.